SCIENTIFIC ANALYSIS OF 21ST CENTURY PRESCHOOL EDUCATION REFORM TERMINOLOGY - Līduma, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The scientific article contains a pedagogical-psychological explanation of the concepts of the pedagogical process used in Preschool education documents. It evaluates the concepts in the regulations of the Cabinet of Ministers and in the methodological materials of the School 2030 reform of the Ministry of Education and Science: collaboration, attitudes, virtues, values, civic participation, customs. Objective of the study. To explain the concepts introduced in the pedagogical process of preschool education from a scientific viewpoint. Research materials and methods: Theoretical: analysis of pedagogical and psychological literature and the regulations of the Cabinet of Ministers and methodological materials of School 2030. Empirical: observations of the pedagogical process in 50 years of continuous work as a teacher are analysed.Research results: The study explains the concepts used in the reform School 2030. It has been found that the child's independent activity in interaction with the competent support of the teacher would be a guarantee for the implementation of the content recommended in the School 2030 methodological documents in practice.